EVALUATION OF ARTIFICIAL INSEMINATION PROGRAM ON LOCAL CATTLE IN PANTE BIDARI DISTRICT, EAST ACEH REGENCY, ACEH PROVINCE - Cut Intan Novita; Muhammad Zika Zika; Eka Meutia Sari (Jurnal Kedokteran Hewan, 2022)
The purpose of this study was to analyze the success of the artificial insemination (AI) program in local cattle in Pante Bidari District, EastAceh Regency, Aceh Province. It was conducted in five villages: Alue Ie Mirah, Buket Bata, Grong-Grong, Meunasah Tunong, and Paya DemamEmpat. The survey method was employed in this study. The respondents were selected by using purposive sampling method. There were 40breeders and 3 inseminators included as the respondents. To be involved in the study, the breeders had to meet certain criteria, such as having anexperience of breeding local cows, at least twice using the AI system. As for the inseminators, they were required to have a permit from the EastAceh Livestock Service. The results showed that the conception rate (CR) was 76.45%; the service per conception (S/C) was 1.22; the calvinginterval (CI) was 12.70 months, and the calving rate (CvR) was 89.92%. This study concluded that the implementation of the artificialinsemination program in Pante Bidari District, East Aceh Regency, has been running effectively.